2020
DOI: 10.1039/d0cy01709d
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the control of selectivity in hydrogenation reactions by confined metal functionalities

Abstract: Confining metal active species in the voids of porous solid matrices such as zeolites, metal-organic frameworks (MOFs), and carbon nanotubes (CNTs) can bring fascinating key advantages in the field of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 162 publications
0
23
0
Order By: Relevance
“…Briefly, Cu 2+ cations first coordinate with polyethylenepolyamine (TEPA) to avoid precipitation under alkaline hydrothermal conditions (pH = 13) during the zeolite synthesis. The as-formed Cu-TEPA complexes could be captured and encapsulated within the voids of the zeolite via the interaction between the metal complex and the zeolite framework . By a subsequent calcination at 550 °C for 6 h in air and reduction at 400 °C for 2 h under 5% H 2 /N 2 atmosphere, well-defined Cu nanoparticles confined in the cavities of the zeolite can be obtained, denoted as Cu@TS-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, Cu 2+ cations first coordinate with polyethylenepolyamine (TEPA) to avoid precipitation under alkaline hydrothermal conditions (pH = 13) during the zeolite synthesis. The as-formed Cu-TEPA complexes could be captured and encapsulated within the voids of the zeolite via the interaction between the metal complex and the zeolite framework . By a subsequent calcination at 550 °C for 6 h in air and reduction at 400 °C for 2 h under 5% H 2 /N 2 atmosphere, well-defined Cu nanoparticles confined in the cavities of the zeolite can be obtained, denoted as Cu@TS-1.…”
Section: Resultsmentioning
confidence: 99%
“…The as-formed Cu-TEPA complexes could be captured and encapsulated within the voids of the zeolite via the interaction between the metal complex and the zeolite framework. 30 By a subsequent calcination at 550 °C for 6 h in air and reduction at 400 °C for 2 h under 5% H 2 /N 2 Scheme 1. Schematic Illustration of the In Situ Encapsulation Approach for the Synthesis of the Cu@TS-1 and Na−Cu@TS-1 atmosphere, well-defined Cu nanoparticles confined in the cavities of the zeolite can be obtained, denoted as Cu@TS-1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, CNT is not only a great catalyst carrier but also an important inorganic nonmetallic catalytic material. [28][29][30] In this work, the obtained Ni@C@CNT catalyst was applied in furfural hydrogenation to THFL. For comparison, Ni@C catalyst derived directly from Ni-MOF was also synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the surface of acid‐treated CNT is rich in oxygen‐containing functional groups, which can effectively adsorb and stabilize metal ions and acid molecules to obtain uniformly dispersed composites. Therefore, CNT is not only a great catalyst carrier but also an important inorganic nonmetallic catalytic material 28–30 . In this work, the obtained Ni@C@CNT catalyst was applied in furfural hydrogenation to THFL.…”
Section: Introductionmentioning
confidence: 99%
“…As solid catalysts, synergistic effects ascribed to the concomitant presence of two metals within nanosized aggregates, nanoclusters or nanoparticles, have been shown to unlock favourable, in some instances unique, catalytic performances in a broad range of conversion processes. [7][8][9][10] Pioneering work in this area by Sinfelt et al in alkane dehydrogenation and hydrogenolysis reactions 11,12 was followed by a surge of studies which demonstrated the potential of bimetallic catalysts in a wide array of reactions, from oxidation, [13][14][15] to hydrogenation, [16][17][18][19][20] reforming, 21 biomass conversion, 5 C-C coupling, 22 or acetoxylation catalysis. 23 The distinctive catalytic properties of bimetallics compared to their monometallic counterparts has been associated to factors such as differences in lattice strain and surface topology, intermetallic charge transfer phenomena, or atomic-scale surface dilution phenomena of one metal within a matrix of second metal (also referred to as single-atom alloys).…”
Section: Introductionmentioning
confidence: 99%